IMPLEMENTASI NILAI NILAI PANCASILA DALAM PENGUATAN KARAKTER BANGSA - Luh Putu Swandewi Antari; Luh De Liska (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
We already know that Pancasila is the basis of the Republic of Indonesia which was established on August 18, 1945. This implies that the system of Indonesian human life, both as individuals and as individuals, as members of society and as people living in the Indonesian state, must refer to the values ​​contained. inside Pancasila. Pancasila is the basis of Indonesian human behavior. The values ​​contained in Pancasila are full of religious values, truth values, goodness values ​​(sila I), human values ​​(sila II), and the beauty and justice values ​​of social life (principle V). Pancasila also contains values ​​that are essential to humans as creatures created by God and that cannot be contested by anyone as an individual, an individual as a member of society and an individual as a citizen. Thought can be established as an effort to reflect carefully and seriously to explore the science and values ​​of Pancasila that have developed in the implementation of education in the era of globalization, and in the end it is formulated in a concept or theory.